Membangun Karakter Mulia pada Anak menurut QS. Luqman 13-19 - Safruroh Safruroh (PSGA LP2M IAIN Pontianak, 2015)
This article elaborates some translations from the translators (mufassir) towards QS. Luqman: 13-19. The verse, furthermore, tells us the efforts done by Luqman al-Hakim to support his children a better education. There are some steps needed to be done to educate his children: aqidah education, religious education, dakwah education, and akhlak education. It is additionally an effort to build the noble character in children.